PERAN KEPALA DESA DALAM MENINGKATKAN MUTU SUMBER DAYA MANUSIA (SDM) MASYARAKAT DI DESA CISALAM KECAMATAN BAROS KABUPATEN SERANG BANTEN - Ade Millatus Sa'adiyyah; Nurasiah Nurasiah (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT The success of a village cannot be separated from the role of the Village Head as a leader in the village, thus the role of the Village Head is very important needed in the process of improving the quality of Human Resources in order to facilitate development, as well as increasing public awareness to participate in improving the quality of human resources. Human Resources in Cisalam Village. In Cisalam Village, Baros District, Serang Regency, the natural resources are very adequate seen from the area of ​​plantations and rice fields with the majority of the people living as farmers, farm laborers, employees and traders. And the Cisalam village community has a low level of education. This study aims to: 1) To determine the role of the village head in improving the quality of human resources in Cisalam Village, Baros District, Serang Regency. 2) To find out what obstacles hinder the role of the village head in improving the quality of human resources in Cisalam Village, Baros District, Serang Regency. The type of research used is descriptive qualitative, namely describing and interpreting existing data to describe reality in accordance with the actual phenomenon. And the results of this study indicate that: 1) The role of the village head in improving the quality of human resources is quite good. 2) Human resources in Cisalam village are still relatively low.